Network science for military coalition operations : information exchange and interaction - Verma, Dinesh, 1964- (Hershey, PA : Information Science Reference, 2010)
'This book is structured into sections that look at some of the challenges related to coalition operations in different types of networks, such as communications and information networks and human and cognitive networks, and looks at other issues that impact the operations of coalitions, the management and use of policies across different organizations'--Provided by publisher.
'Premier reference source.'--Cover.
Includes bibliographical references and index.
Keywords: Combined operations (Military science); Communications, Military; Computer networks; Information networks; Cognitive radio networks; Social networks; United States -- Armed Forces -- Information services; Great Britain -- Armed Forces -- Information services